Pore Connectivity Characterization Using Coupled Wood’s Metal Intrusion and High-Resolution Imaging: A Case of the Silurian Longmaxi Shales From the Sichuan Basin, China - Yu, Lingjie; Liu, Keyu; Fan, Ming; Pan, Zhejun (Frontiers in Earth Science, 2021)
Pore connectivity is crucial for shale gas production. However, the three-dimensional (3D) characteristics and distribution of pore networks, and more fundamentally, the underlying role of different pore types on pore connectivity in shales are inadequately understood. By comparing 3D pore connectivity derived from direct microstructural imaging of pores filled with Wood’s metal at a pressure corresponding to the finest accessible pore throat in the resolution ranges that may be achieved by X-ray micro-CT and SEM, it is possible to evaluate pore connectivity of different type shales. The pore connectivity of three shales including a mixed mudstone, siliceous shale and argillaceous shale from the Silurian Longmaxi Formations is investigated via combined broad ion beam (BIB) polishing, and SEM and micro- X-ray micro-CT imaging after Wood’s metal injection at a pressure up to 380 MPa. The three shales show significant differences in pore connectivity. The mixed mudstone shows an excellent pore connectivity in the matrix; the siliceous shale shows an overall poor connectivity with only a small amount of OM (organic matter) pores immediately adjacent to micro fractures displaying interconnectivity; while the pores in the argillaceous shale, dominated by plate-like clay pores, are largely not interconnected.